ANALISA PERENCANAAN SISTEM DRAINASE DALAM UPAYA PENANGGULANGAN BANJIR DI KECAMATAN GANDUSARI KABUPATEN TRENGGALEK - Rizqi Dwi Prasetyo; Yosef Cahyo; Ahmad Ridwan (Jurnal Manajemen Teknologi & Teknik Sipil, 2019)
In industrial areas or densely populated settlements, generally found channels that function besides to drain rainwater as well as to discharge domestic wastewater or dirty water from households. Drainage systems are often the main problem in the occurrence of flooding. It is necessary to analyze how their performance and resistance to flooding in the District of Gandusari, Trenggalek Regency. For analysis of drainage system planning in flood prevention efforts, the authors used the Van-Breun and Mononobe calculation methods to determine the number of incoming water discharge, the ideal dimension of the channel to accommodate the inlet discharge channel, and calculate the cost budget plan (RAB) of the builder. From the analysis, results obtained a cumulative discharge of rainwater, and dirty water entering the drainage amounted to 0.4695 m3 / sec. From the calculation, the ideal dimensions of the drainage can be obtained to be able to accommodate rainwater runoff and dirty water discharge using square channels, where the 1.5 m channel height is all added to the water level of 0.2 m and 0.7 m in width 500 m. While the budget plan for the construction costs is Rp. 794,048,000.00 -Di daerah industri atau pemukiman padat penduduk umumnya ditemukan saluran yang berfungsi selain untuk mengalirkan air hujan juga sekaligus untuk pembuangan air limbah domestik ataupun air kotor dari rumah tangga. System drainase sering menjadi pokok masalah dalam terjadinya banjir, maka perlu di Analisa bagaimana kinerjanya dan ketahanan terhadap banjir di Kecamatan Gandusari Kabupaten Trenggalek. Untuk analisis perencanaan sistem drainase dalam upaya penanggulangan banjir penulis menggunakan metode perhitungan Van-Breun dan Mononobe untuk mengetahui angka debit air yang masuk, dimensi ideal saluran untuk menampung saluran debit air masuk dan menghitung rencana anggaran biaya (RAB) pembangunanya. Dari hasil analisa didapatkan debit komulatif air hujan dan air kotor yang masuk ke drainase sebesar 0.4695 m3/detik. Dari perhitungan didapatkan dimensi saluran drainase yang ideal agar mampu menampung limpasan air hujan dan debit air kotor dengan menggunakan saluran berbentuk persegi, dimana tinggi saluran 1,5 m semuanya ditambahkan dengan tinggi jagaan air sebesar 0,2 m dan lebar 0,7 m dengan panjang 500 m. Sedangkan rencana Anggaran Biaya pembangunannya sebesar Rp. 794.048.000,00,-